Personality and Emotion Regulation Strategies - Esti Hayu Purnamaningsih (Universidad de San Buenaventura, 2017)
The emotions has many important functions in our life such as in relation of interpersonal communication, and health. In interpersonal communicative function aimed to signal to other information about internal state. Emotions manifests in specific cognitive, behavioural, and physiological reactions, thus closely related to health. There is wide variety of ways for individuals to regulate their emotion. In this regard, there are two kindsof emotion regulation strategy; first Antecedent-focused emotion regulation consisting of situation selection, situation modification, attentional deployment, cognitive change and second, Response-focused emotion regulation consisting of suppression. The purpose of this research is to investigate personality factors relatewith emotion regulation strategies. 339 students from Faculty of Psychology, Universitas Gadjah Mada were participating in this study and given The Big Five Personality Factors (Ramdhani, 2012, adaptation), and the modified version of the Emotion Regulation Scale was used, Emotion Regulation Questionnaire (John & Gross,2004) which measure personality and emotion regulation respectively. Using multiple regression analysis, the study indicated that personality predicts emotion regulation strategies.